Waldenström's Macroglobulinemia - Leblond, Véronique; Treon, Steve; Dimoploulos, Meletios (Springer International Publishing : Imprint: Springer, 2017)
This book sheds new light on clinical, biological and therapeutic data on the rare disease Waldenström's Macroglobulinemia (WM) with the participation of widely-recognized experts, involved in this field. It represents the efforts of physicians, scientists and patients, all around the world, to better understand and cure this rare disease. Considerable advances in the diagnosis, treatment indications, response criteria, prognostic factors and treatment options have been made since Dr Jan Waldenström first reported this "new syndrome" 70 years ago. Particularly instrumental in advancing of our understanding of WM have been the eight international workshops devoted to this disease. New, exciting molecular data have recently been reported, allowing us to revisit the oncogenic events leading to WM B-cell proliferation and to use newly available compounds targeting oncogenic pathways.- Resumé vydavatel
Keywords: hematologie; imunologie; maligní nemoci krve; non-Hodgkinův lymfom; hematology; immunology; blood cancer; non-Hodgkin's lymphomas; elektronické knihy; kolektivní monografie; electronic books; collective monographs